Deconstructing subjective unmet healthcare needs: a South Korean case study with policy implications - Chung, Woojin (Frontiers in Public Health, 2024)
Background: Despite widespread efforts by many countries to reduce the prevalence of unmet healthcare needs within their populations, there remains a scarcity of research systematically exploring the components of these needs.Objectives: This study aims to deconstruct subjective unmet healthcare needs into two distinct components: the experience of subjective healthcare needs (the "Needs" component) and the experience of unmet needs contingent on those healthcare needs (the "Unmet" component).Methods: This analysis utilizes data from 13,359 adults aged 19 or older, collected through the 2018 Korea Health Panel survey, with the aim of minimizing the influence of the coronavirus disease 19 pandemic. The two dependent variables are the experience of subjective healthcare needs and whether these needs have been met. The independent variables include 15 socio-demographic, health, and functional characteristics. The study employs both a population proportion analysis and a multivariable bivariate probit model with sample selection.Results: In South Korea, 11.6% (CI [confidence interval] = 11.0-12.3%) of the population experienced subjective unmet healthcare needs. Upon deconstructing these, 96.7% (CI = 96.2-97.1%) of the population exhibited the Needs component, and 12.0% (CI = 11.4-12.7%) displayed the Unmet component. Each independent variable showed different associations between the two components. Furthermore, effective interventions targeting the characteristics associated with each component could reduce the proportion of the population experiencing subjective unmet healthcare needs from 11.6% to 4.0%.South Korea faces a significant challenge with a high prevalence of subjective unmet healthcare needs. To tackle this challenge successfully, the universal healthcare coverage system should adapt its approach based on the characteristics associated with each component of subjective unmet healthcare needs. To achieve this effectively, it is recommended that the government prioritize strengthening community-based primary healthcare, which currently lacks sufficient resources.The abstract needs to be rewritten, especially clarify the objetives, after background. I have revised the abstract to clarify the study's objectives.